DIISC-IV. DIISCovery of Anomalously Low Metallicity H ii Regions in NGC 99: Indirect Evidence of Gas Inflows - Alejandro J. Olvera; Sanchayeeta Borthakur; Mansi Padave; Timothy Heckman; Hansung B. Gim; Brad Koplitz; Christopher Dupuis; Emmanuel Momjian; Rolf A. Jansen (The Astrophysical Journal)
As a part of the Deciphering the Interplay between the Interstellar medium, Stars, and the Circumgalactic medium (DIISC) survey, we investigate indirect evidence of gas inflow into the disk of the galaxy NGC 99. We combine optical spectra from the Binospec spectrograph on the MMT telescope with optical imaging data from the Vatican Advanced Technology Telescope, radio H i 21 cm emission images from the NSF Karl G. Jansky’s Very Large Array, and UV spectroscopy from the Cosmic Origins Spectrograph on the Hubble Space Telescope. We measure emission lines (H α , H β , [O iii ] λ 5007, [N ii ] λ 6583, and [S ii ] λ 6717, 31) in 26 H ii regions scattered about the galaxy and estimate a radial metallicity gradient of −0.017 dex kpc ^−1 using the N2 metallicity indicator. Two regions in the sample exhibit an anomalously low metallicity (ALM) of 12 + log(O/H) = 8.36 dex, which is ∼0.16 dex lower than other regions at that galactocentric radius. They also show a high difference between their H i and H α line of sight velocities on the order of 35 km s ^−1 . Chemical evolution modeling indicates gas accretion as the cause of the ALM regions. We find evidence for corotation between the interstellar medium of NGC 99 and Ly α clouds in its circumgalactic medium, which suggests a possible pathway for low metallicity gas accretion. We also calculate the resolved Fundamental Metallicity Relation (rFMR) on subkiloparsec scales using localized gas-phase metallicity, stellar mass surface density, and star formation rate surface density. The rFMR shows a similar trend as that found by previous localized and global FMR relations.